Study of structural, optical properties and electronic structure of PTCDI-C5 organic nanostructure - Kurban, M.; Gündüz, Bayram (Elsevier B.V., 2018)
This work reports the change in the structural, electronic, spectroscopic and optical properties of N,N?-Dipentyl-3,4,9,10-perylenedicarboximide (PTCDI-C5) small molecule via experimental and theoretical techniques. Experimental and simple models were taken into consideration to calculate the refractive index (n) of PTCDI-C5 from its energy gap (Eg) data. Electrical conductance was recorded. UV, FT-IR and FT-Raman spectra characteristics and the electronic properties of PTCDI-C5 were also recorded time-dependent (TD) DFT approach based on optimized structure with different solvent environments. The results herein obtained reveal that PTCDI-C5 material is suitable for UV and chemical sensors due to its good optoelectronic paramaters. © 2017 Elsevier B.V.
Keywords: Density-functional theory; Electrical conductivity; Electronic structure; Optical properties; Organic nanostructures; Refractive index